Take me out to the ballgame?: Situational crisis communication theory and the effects of the COVID-19 pandemic on the 2020 Major League Baseball season - Bolin, A. F. (ProQuest Dissertations Publishing, 2021)
This dissertation examines Major League Baseball (MLB) crisis communication response strategies to the COVID-19 Pandemic during the abbreviated 60-game 2020 MLB season. Using Timothy Coombs` (2007a) Situational Crisis Communication Theory and Brown-Devlin and Brown`s (2020) Sports Crisis Typologies, this study seeks to determine the relationship fans sports identification has on individuals` perception of MLB`s response to the COVID-19 Pandemic. Through the use of content analysis, this study identified six distinct crisis communication strategies used by MLB via their online communication channels, Attacking the Accuser, Compensation, Justification, Reminding, Scapegoating, and Victimage. Through a statistical survey, this research is able to demonstrate that individuals` sports identification was a significant predictor of participants` positive perception of MLB`s response to the COVID-19 Pandemic. This research identified two distinct categories of sports identification, Sports Identification - Time and Sports Identification Connection. Sports identification helps explain how individuals see themselves as connected to a professional athlete, sports team, and/or league.